Antibiotic Resistance: What are the Opportunities for Primary Care in Alleviating the Crisis? - Hansen, Malene Plejdrup; Hoffmann, Tammy C.; McCullough, Amanda R.; van Driel, Mieke L.; Del Mar, Chris B. (Frontiers in Public Health, 2015)
Numerous opportunities are available in primary care for alleviating the crisis of increasing antibiotic resistance. Preventing patients from developing an acute respiratory infection (ARI) will obviate any need for antibiotic use downstream. Hygiene measures such as physical barriers and hand hygiene, and possibly vaccination and exercise, may be effective. Also, a large range of complementary and alternative medicines (e.g. zinc, vitamin C and probiotics) are proposed for preventing and treating ARIs, but evidence for efficacy is scarce. General practitioners’ (GPs) attitudes towards antibiotic prescribing are a major factor in the prescribing for ARIs. Professional interventions with educational components are effective, although they have modest effects, and are expensive. GPs’ perceptions – that mistakenly assume as a default that patients want antibiotics for their ARIs – are often wrong. Shared decision making might be a solution, as it enables clinician and patient to participate jointly in making a health decision, having discussed the options together with the evidence for their harms as well as benefits. Furthermore, GPs’ diagnostic uncertainty – often leading to an antibiotic prescription “just in case” – might be addressed by exploiting strategies such as safety-netting, e.g., establishing with the patient a priori clearly defined actions to take if the course of the illness deviates from the expected. None of these strategies or interventions on their own will greatly improve the use of antibiotics for ARIs. However, used in concert, combinations are likely to enable clinicians and health care systems to implement the strategies that will reduce antimicrobial resistance in the future.